2019
DOI: 10.1111/ajco.13160
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among prostate cancer survivors in South Korea: A nationwide population‐based, longitudinal study

Abstract: Aim This time‐dependent study aimed to analyze the prevalence of psychological distress in prostate cancer survivors by using claims data in South Korea. Methods In a nationwide cohort, 32 005 patients were identified who were diagnosed with prostate cancer between January 2010 and December 2014. We referred the diagnostic codes of mental disorders as psychological distress. We categorized the prevalence of psychological distress based on age and specific times before and after the cancer diagnosis. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…While other authors in similar environment reported prevalence rates ranging from 17-28% for depression [5,6]. On the other hand, some authors reported a much higher prevalence rates for anxiety disorder (28-39%) [7,8]. Reasons for the varying prevalent rates among the various studies could be because of the instrument used in assessing for psychiatric morbidity, or the different populations been studied.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…While other authors in similar environment reported prevalence rates ranging from 17-28% for depression [5,6]. On the other hand, some authors reported a much higher prevalence rates for anxiety disorder (28-39%) [7,8]. Reasons for the varying prevalent rates among the various studies could be because of the instrument used in assessing for psychiatric morbidity, or the different populations been studied.…”
Section: Resultsmentioning
confidence: 94%
“…Another study had reported much higher prevalence of 33% [7]. Anxiety disorders prevalence between 28% and 39% were reported by various authors [7,8].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…2021A maior frequência de pacientes com estado civil casado (13 -69,1%) na amostra também pode ter contribuído para os resultados descritos, haja vista que, segundo Vieira, Araújo e Vargas (2012), a figura da esposa como cuidadora ou participante no processo de tratamento auxilia no enfrentamento da doença e resulta em menor repercussão afetiva.Outro destaque neste contexto é a afirmação de crença espiritual e religiosa dos homens entrevistados neste estudo (20 -95,24%), a qual, segundoFerrão (2015), pode contribuir para a manutenção de papeis familiares e sociais durante o tratamento do CP Na escala funcional, o domínio que apresentou maior comprometimento na QV, foi a função emocional com média de 73,78. As perguntas 21, 22, 23 e 24 do instrumento EORTC QLQ C-30 compõem essa escala e abordam condições de nervosismo, preocupação, irritabilidade e depressão.Seeman et al (2018), por meio da investigação da influência dos sintomas depressivos na QV de pacientes com câncer de próstata, apontou resultados semelhantes em itens correspondentes à sensação de estar deprimido.Comparado a outros domínios de funcionalidade, isso revela maior vulnerabilidade na escala emocional Heo et al (2020). concluiu que o sofrimento psicológico em sobreviventes do CP tem variação de sua prevalência no decorrer do processo terapêutico.Por isso, o diagnóstico e as intervenções dirigidas à saúde mental podem promover melhorias na qualidade de vida dos sobreviventes do CP Occhipinti (2019).…”
unclassified